ZARAFSHON TOG‘ TIZMASINING JANUBIY YON BAG‘RIDA TARQALGAN QURUQLIK MOLLYUSKALARNING ZOOGEOGRAFIK TAVSIFI - Orziyeva Y.M., Orziyeva Y.M. (Actual problems and prospects of the study of the fauna, 2024)
The terrestrial molluscs distributed on the southern flank of the Zarafshan mountain range have been found to contain 35 species belonging to 13 families and are part of the following zooeographic groups: Poleactic and Holoarctic, European, mountainous Asian, Mediterranean, pre Asian and Mediterranean species.